Themes and Critical Debates in Contemporary Journalism. - Rupar, Verica (Cambridge Scholars Publishing, 2017)
The old definitions of journalism are under fire; its occupational identity and importance to democracy, public life, and social justice are contested, while the content, technologies, practices and cultural conditions of production of news are changing. Contemporary developments signal significant shifts in the ways journalism is practiced, conceptualized and taught. This book, written in the context of the World Journalism Education Congress (WJEC) held in 2016 at Auckland University of Technology, New Zealand, offers a collection of essays on some of the key concepts, categories and models.